Morphological and taxonomic reexamination on a crocodile newt recently described from Japan (Urodela, Salamandridae, Echinotriton) - Nishikawa, Kanto; Matsui, Masafumi; Tominaga, Atsushi (Zootaxa, 2022)
A crocodile newt, Echinotriton raffaellii, recently described from the Amami islands in the Ryukyu archipelago, western Japan has been regarded as Amami lineage of E. andersoni from the Okinawa islands, to which it is morphologically very similar, but genetically divergent. In the original description of E. raffaellii, only two specimens, including one born in captivity, were examined and only limited morphological comparisons with E. andersoni were made. Here we examined the morphological characteristics of E. raffaellii with an ample set of specimens, compared them with those of E. andersoni, and clarified their independent specific statuses.